Studien zur Systematik und Taxonomie der Gattung Hylaeus F. (Apidae, Colletinae). 2. Klärung und Neubeschreibung von Arten arabischer Länder. - Dathe, Holger H. (Contributions to Entomology = Beiträge zur Entomologie, 1995)
As the first part of a new treatment of the bee fauna of Arab countries, twelve Hylaeus F. species are revised. Studying syntypes of Walker’s species, Hylaeus (Paraprosopis) klugii (Friese, 1898) was recognized as a synonym of H. (Paraprosopis) albonotatus (Walker, 1871); H. (Paraprosopis) dinkleri (Friese, 1898) is a different species. The status of these 3 taxa and of Prosopis falsifica Alfken, 1930 is fixed by designation of lectotypes. Four species are new: Hylaeus (Paraprosopis) donbakeri (male, female), H. (Paraprosopis) omanicus (male), H. (Hylaeus) hameri (male, female) and H. (Spatulariella) fossifer (male, female). The types are deposited at DEI Eberswalde. Descriptions and illustrations of the male of H. (Prosopis) laevithorax (Alfken, 1924) and the female of H. (Lambdopsis) melba (Warncke, 1992) are provided for the first time. Redescriptions, including diagnosis, illustrations and geographical records, are given for the following species: H. (Paraprosopis) elatus (Warncke, 1981), H. (Paraprosopis) gribodoi (Vachal, 1895), H. (Paraprosopis) lactipennis (Benoist, 1957) and H. (Hylaeus) beaumonti (Benoist, 1958). Nomenclatural Acts albonotatus (Walker, 1871) (Hylaeus (Paraprosopis)), Lectotype described as Prosopis albonotata dinkleri (Friese, 1898) (Hylaeus (Paraprosopis)), Lectotype described as Prosopis dinkleri donbakeri Dathe, 1995 (Hylaeus (Paraprosopis)), spec. n. hameri Dathe, 1995 (Hylaeus (Paraprosopis)), spec. n. melba (Warncke, 1992) (Hylaeus (Paraprosopis)), comb. n. hitherto Prosopis (Nesoprosopis) melba omanicus Dathe, 1995 (Hylaeus (Paraprosopis)), spec. n. fossifer Dathe, 1995 (Hylaeus (Spatulariella)), spec. n. falsifica Alfken, 1930 (Prosopis), Lectotype now a synonym of Hylaeus (Paraprosopis) dinkleri (Friese, 1898) klugii Friese, 1898 (Prosopis), Lectotype now a synonym of Hylaeus (Paraprosopis) albonotatus (Walker, 1871) kermana Warncke, 1981 (Prosopis klugi), syn. n. of Hylaeus (Paraprosopis) albonotatus (Walker, 1871) mesopotamae Warncke, 1992 (Prosopis klugii), syn. n. of Hylaeus (Paraprosopis) albonotatus (Walker, 1871)